Genomic instability may originate from imatinib-refractory chronic myeloid leukemia stem cells - Bolton-Gillespie, Elisabeth; Schemionek, Mirle; Klein, Hans-Ulrich; Flis, Sylwia; Hoser, Grazyna; Lange, Thoralf; Nieborowska-Skorska, Margaret; Maier, Jacqueline; Kerstiens, Linda; Koptyra, Mateusz; Müller, Martin C.; Modi, Hardik; et al. (Blood, 2013)
Genomic instability is a hallmark of chronic myeloid leukemia in chronic phase (CML-CP) resulting in BCR-ABL1 mutations encoding resistance to tyrosine kinase inhibitors (TKIs) and/or additional chromosomal aberrations leading to disease relapse and/or malignant progression. TKI-naive and TKI-treated leukemia stem cells (LSCs) and leukemia progenitor cells (LPCs) accumulate high levels of reactive oxygen species (ROS) and oxidative DNA damage. To determine the role of TKI-refractory LSCs in genomic instability, we used a murine model of CML-CP where ROS-induced oxidative DNA damage was elevated in LSCs, including quiescent LSCs, but not in LPCs. ROS-induced oxidative DNA damage in LSCs caused clinically relevant genomic instability in CML-CP–like mice, such as TKI-resistant BCR-ABL1 mutations (E255K, T315I, H396P), deletions in Ikzf1 and Trp53, and additions in Zfp423 and Idh1. Despite inhibition of BCR-ABL1 kinase, imatinib did not downregulate ROS and oxidative DNA damage in TKI-refractory LSCs to the levels detected in normal cells, and CML-CP–like mice treated with imatinib continued to accumulate clinically relevant genetic aberrations. Inhibition of class I p21-activated protein kinases by IPA3 downregulated ROS in TKI-naive and TKI-treated LSCs. Altogether, we postulate that genomic instability may originate in the most primitive TKI-refractory LSCs in TKI-naive and TKI-treated patients. •Imatinib does not prevent accumulation of genomic instability in CML-CP.•Imatinib-refractory leukemia stem cells may be a source of genomic instability in CML-CP.